REGULATING NATIONAL ECONOMIC ACTIVITIES THROUGH TRADE: A NORMATIVE ANALYSIS OF THE STATE'S ROLE IN REGULATING MARKETS, MAINTAINING FAIR DISTRIBUTION, AND REALISING PUBLIC WELFARE (LITERATURE REVIEW) - Gunawan Widjaja (CV. Adiba Aisha Amira, 2026)
This study analyses trade law regulations as instruments for controlling national economic activities through a normative juridical approach based on literature review, focusing on Law No. 7 of 2014 on Trade as a constitutional derivative of Article 33 of the 1945 Constitution. The first discussion reveals the role of the state in regulating the market through the harmonisation of interregional regulations, control of strategic goods, supervision of e-commerce, and commodity futures markets for economic efficiency and stability. The second discussion evaluates the contribution of trade regulations to distributive justice through the stabilisation of basic commodity prices, the empowerment of MSMEs, the protection of farmers, and synergy with the KPPU, which succeeded in reducing the Gini coefficient from 0.388 (2020) to 0.379 (2025). The findings confirm that national trade regulations are effective in achieving public welfare, although they require digital governance reforms and geopolitical adaptation for the Indonesia Emas 2045 vision. This study recommends strengthening the digital single window, ASEAN harmonisation, and optimising strategic distribution state-owned enterprises.